Multiple segmental absence of intestinal musculature presenting as spontaneous isolated perforation in an extremely low-birth-weight infant. - Oretti, Chiara; Bussani, Rossana; Janes, Augusta; Demarini, Sergio (J Pediatr Surg, 2010)
Defect of the intestinal musculature is a rare condition. It may cause intestinal perforation or obstruction. It manifests itself mainly in the neonatal period and usually affects preterm infants. We describe one such case, which was first diagnosed as a spontaneous isolated intestinal perforation. Emergency laparotomy was performed and showed multiple perforations, with accompanying peritonitis and ascites. Pathologic examination showed partial or complete absence of the musculature, particularly of the inner circular layer, with fibrous tissue in the regions of missing muscle, and abnormal vasculature. The myenteric plexus was absent in areas of muscle loss but present in other sites. These findings suggest that the absence of muscle may not represent a congenital malformation but may be secondary to ischemic injury.
Keywords: Diseases in Twins; Female; Humans; Ileum; Infant, Extremely Low Birth Weight; Infant, Newborn; Infant, Premature; Intestinal Atresia; Intestinal Perforation; Laparotomy; Muscle, Smooth; Myenteric Plexus; Rare Diseases